(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The COVID-19 pandemic has wreaked havoc on the Philippines regarding personal and family finances. Almost every family has been affected by the economic slump, with many claiming that financial stress affects their mood, mental health, and sleep. As the infection spread, many families lost their primary source of income. The continuation of the new normal of education impacts college students’ financial ability to pay their tuition because most parents have lost their jobs, which is a major factor in how they will finance their children’s expenses. This study aimed to see the Effects of the Pandemic on the family financial status among 3rd-year BTVTED students of Bestlink College of the Philippines-Bulacan AY 2021-2022 as they pursue their degrees. The researchers in this research paper are looking forward to selecting Third Year BTVTED to finance their academic expenses and continue pursuing their baccalaureate degree despite the COVID-19 pandemic up to this point. Researchers used the design of normative, descriptive methods for research to gather information from respondents selected by the researcher in determining the Effects of the Pandemic on the family financial status among 3rd-year BTVTED students of Bestlink College of the Philippines-Bulacan AY 2021-2022. Researchers also used targeted sampling to study and selected twenty-five BTVTED third-year students. This study shows that 44 percent of third-year BTVTED students’ family income is sufficient to sustain their needs before the community lockdown, while the others are not. And 44 percent are not financially stable nowadays, and their family doesn’t have enough money to support their needs, while the rest have sufficient finances. Third-year BTVTED student’ budget for food, house bills, and educational funds is sufficient to sustain their family’s monthly income. Many families lose their jobs or source of income, resulting in a financial crisis. Fifty-two per cent of the respondents agree to receive financial assistance from the government. The strategy in budgeting finances helps the respondents during the pandemic, and respondents are 48 percent neutral. Most third-year BTVTED students’ families learned to save money for emergencies because of the pandemic. As a result, saving money can save you and your family for emergencies.